422 Preclinical drug screen leads to clinical trial for treatment of hypoglycemia unawareness in type 1 diabetes mellitus - Micah Devore; Ashley N. Iles; Lily A. Schoeder; Megan B. Music; Bansi V. Patel; Ashlee R. Marksbury; Mason M. Wooten; Andrea M. Woodcox; Zachary Beckner; Erica L. Macon; Simon J. Fisher (Journal of Clinical and Translational Science)
Objectives/Goals: People with insulin-treated diabetes face hypoglycemia risk due to imperfect insulin replacement and impaired counterregulation. We identified the dopamine antagonist, metoclopramide, as a potential treatment. Hypothesis: Treatment with metoclopramide will prevent the development of impaired counterregulatory response to hypoglycemia. Methods/Study Population: In a pre-clinical model, diabetes was induced in 10-week-old Sprague-Dawley rats with streptozotocin (STZ, 65 mg/kg IP). Rats were divided into three groups: 1) diabetic controls (STZ+RS, n = 6), 2) recurrent hypoglycemia (STZ+RH, n = 7), and 3) recurrent hypoglycemia + metoclopramide (STZ+RH+MET, 3 mg/kg IP, n = 7). After 3 days, all rats underwent a hyperinsulinemic (50 mU/kg/min) and hypoglycemic (~45 mg/dl) clamp. In the clinical trial, adults with Type 1 diabetes (age 20–60, ≥5 years duration) were enrolled in a phase II, double-blinded, placebo-controlled trial. Awareness status was assessed via Gold score, and subjects maintained drug regimens and underwent two hyperinsulinemic-hypoglycemic clamps (where blood glucose was lowered to 100, 65, 55, and 45 mg/dl) to assess counterregulation. Results/Anticipated Results: In the pre-clinical model, glucose infusion rates (GIR) to maintain hypoglycemia were higher in STZ+RH (27±0.9 mg/kg/min) than STZ+RS (19±0.8 mg/kg/min, p Discussion/Significance of Impact: Metoclopramide improves glucoregulatory, sympathoadrenal, and counterregulatory responses to hypoglycemia in pre-clinical models, suggesting dopaminergic regulation. While clinical data are still blinded, increased epinephrine and growth hormone responses suggest treatment may preserve or restore counterregulation.